BALI DALAM PENGEMBANGAN PENGOBATAN TRADISIONAL KOMPLEMENTER (Kajian Yuridis Peraturan Menteri Kesehatan Republik Indonesia Nomor 15 Tahun 2018 Tentang Penyelenggaraan Pelayanan Kesehatan Tradisional Komplementer) - Bagiastra, I Nyoman; Sudantra, I Ketut (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2018)
Traditional medicine by the people in several regions in Indonesia is very diverse. Communities in a particular area have different ways and techniques in traditional medicine, this is because culture and understanding and also the biodiversity found in the environment in which they live and the local wisdom they have is the cause of the emergence of various cultural products. Given that Bali has a culture related to the understanding of traditional medicine since ancient times, inherited from generation to generation, it has the potential to carry out complementary traditional medicine that has local wisdom. Usadha was populist in Bali carried out by a balian. There are several types of balian that are contained in the palm bodon ejection in accordance with the field and purpose. Normatively, the government has issued Regulation of the Minister of Health of the Republic of Indonesia Number 15 of 2018 concerning the Implementation of Complementary Traditional Health Services as a basis for implementing complementary traditional medicine. There are provisions that need to be studied and criticized so that they do not have the potential to hinder if Bali carries out complementary traditional medicine services in the future.